Knockdown of Kremen2 Inhibits Tumor Growth and Migration in Gastric Cancer - Chen, Beibei; Wang, Sai-Qi; Huang, Jinxi; Xu, Weifeng; Lv, Huifang; Nie, Caiyun; Wang, Jianzheng; Zhao, Huichen; Liu, Yingjun; Li, Jitian; Lu, Canrong; Zhang, Jianying; et al. (Frontiers in Oncology, 2021)
Kremen2 (Krm2) plays an important role in embryonic development, bone formation, and tumorigenesis as a crucial regulator of classical Wnt/β-catenin signaling pathway. However, the role of Krm2 in gastric cancer is not clear. The aim of this study was to explore the regulatory role of Krm2 in the tumorigenesis and metastasis of gastric cancer. It was demonstrated that, compared to para-cancerous tissues, Krm2 was significantly up-regulated in gastric cancer tissues and was positively correlated with the pathological grade of gastric cancer patients. Given that Krm2 is abundantly expressed in most tested gastric cancer cell lines, Krm2 knockdown cell models were established and further used to construct mice xenograft model. After knocking down Krm2, both the cell survival in vitro and tumorigenesis in vivo of gastric cancer cells were inhibited. At the same time, knockdown of Krm2 induced apoptosis, cell cycle arrest at G2/M phase and repression of migration in gastric cancer cells in vitro. Mechanistically, we found that knockdown of Krm2 suppressed PI3K/Akt pathway. Therefore, we revealed the novel role and the molecular mechanism of Krm2 in promoting the tumorigenesis and metastasis in gastric cancer. Krm2 can be a potent candidate for designing of targeted therapy.